Case Report: The first Korean familial case of BCAP31-related deafness, dystonia, and cerebral hypomyelination - Suh, Yoong-A; Hwang, Jisun; Seo, Go Hun; Khang, Rin; Lee, Jang Hoon; Park, Moon Sung; Sohn, Young Bae (Frontiers in Pediatrics, 2025)
Deafness, dystonia, and central hypomyelination (DDCH) syndrome (OMIM #300475) is a rare X-linked genetic disorder characterized by developmental delays, deafness, central hypomyelination, and dystonia. We report the first Korean familial case involving twin boy and girl carrying a novel pathogenic BCAP31 variant which was inherited from their mother. The male proband, born prematurely with very low birth weight (VLBW), exhibited severe global developmental delay, microcephaly, failure to thrive, dystonia, seizures, sensorineural hearing loss (SNHL) requiring cochlear implantation, and mild facial dysmorphism. A brain MRI revealed white matter atrophy, thinning of the corpus callosum, and delayed myelination. The twin sister presented with mild developmental delays and bilateral SNHL but did not experience seizures or dystonia. Their mother also had bilateral SNHL. Whole genome sequencing identified a hemizygous pathogenic variant, c.247C>T (p.Gln83Ter), in the BCAP31 in the proband. The variant was also found in his mother and twin sister, who exhibited less severe symptoms. Early genetic evaluation via next-generation sequencing is crucial for timely diagnosis and intervention, particularly in VLBW infants with genetic disorders. This report expands the understanding of genotype-phenotype correlations in DDCH syndrome and highlights the variable phenotypes in manifesting females.